Penggunaan Alat Peraga untuk Meningkatkan Hasil Belajar Siswa Kelas V SD N 2 Gunung Katun Kecamatan Baradatu - Yunita Wildaniati (Jurnal Dewantara, 2019)
The problem in this study is the still low learning outcomes of fifth grade students of Gunung Katun 2 Elementary School in District Baradatu. The aim is to improve the learning outcomes of students in the fifth grade mathematics lesson. The method used in this study is Classroom Action Research. The subjects of this study were the fifth grade totaling 19 students. The data analysis technique used is the quantitative method and then translated into qualitative descriptive. The results of this study indicate that the use of teaching aids in learning mathematics can improve student learning outcomes. This can be seen the learning outcomes of students in the first cycle the average value of 69 and the second cycle experienced an increase in the average value of 74 with completeness in the first cycle 68% and in the second cycle increased to 79%.